Mechanisms of acquired resistance to 2-(4-aminophenyl)benzothiazole (CJM 126, NSC 34445) - Bradshaw, T D (Nature Publishing Group, 2000)
2-(4-aminophenyl)benzothiazole (CJM 126) elicits potent growth inhibition in human-derived breast carcinoma cell lines, including oestrogen receptor-positive (ER+) MCF-7(wt)cells. Analogues substituted in the 3′ position with I (DF 129), CH (3)(DF 203), or CI (DF 229) possess an extended profile of antitumour activity with remarkable selective activity in cell lines derived from solid tumours associated with poor prognosis, e.g. breast, ovarian, renal and colon. Growth inhibition occurs via unknown, possibly novel mechanism(s) of action. Two cell lines have been derived from sensitive MCF-7(wt)breast cancer cells (IC (50) value < 0.001 μM) following long-term exposure to 10 nM or 10 μM CJM 126, MCF-7(10 μM 126) and MCF-7(10 μM 126)respectively, which demonstrate acquired resistance to this agent (IC (50)> 30 μM) and cross-resistance to DF 129, DF 203 and DF 229. Sensitivity to tamoxifen, benzo[a]pyrene (BP), mitomyin C, doxorubicin and actinomycin D is retained. Resistance may, in part, be conferred by the constitutively increased expression of bcl-2 and p53 proteins detected in MCF-7(10 nM 126)and MCF-7(10 μM 126)lysates. Significantly decreased depletion of CJM 126 (30 μM) from nutrient medium of MCF-7(10 nM 126)cells was observed with predominantly cytoplasmic drug localization and negligible DNA strand breaks. N -acetyl transferase (NAT)1 and NAT2 proteins were expressed by all three MCF-7 sub-lines, but significantly higher expression of NAT2 was accompanied by enhanced acetylation efficacy in MCF-7(10 nM 126)cells. In contrast, CJM 126 (30 μM) was rapidly depleted from nutrient medium of MCF-7(10 μM 126)culture and accessed nuclei of these cells exerting damage to DNA. The major biotransformation product of CJM 126 in MCF-7(10 μM 126)cells was 2-(4-aminophenyl)-6-hydroxybenzothiazole (6-OH 126). This metabolite possessed no antitumour activity. Accordingly, in this sub-line, low constitutive expression and activity of cytochrome P450 (CYP) 1A1 was detected. © 2000 Cancer Research Campaign